2002
DOI: 10.2337/diabetes.51.5.1409
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor-1α Recruits the Transcriptional Co-Activator p300 on the GLUT2 Gene Promoter

Abstract: Mutations in the hepatocyte nuclear factor (HNF)-1␣ gene have been linked to subtype 3 of maturity-onset diabetes of the young (MODY), a disease characterized by a primary defect in insulin secretion. Here we show that the human GLUT2 gene is closely regulated by HNF-1␣ via sequences downstream of the transcriptional start site by interaction with transcriptional co-activator p300. The promoter region of the human GLUT2 gene was subcloned into luciferase expression plasmids that were transfected together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 30 publications
(21 reference statements)
3
65
0
Order By: Relevance
“…The results indicated that p300 did not enhance NF1-and HNF1␣-mediated activation of the L-PK promoter. 3 The reason for this is unclear, because p300 has been reported to interact with the activation domain of HNF1␣ (39). However, it is possible that other co-activators are involved in cooperative activation of the L-PK gene.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The results indicated that p300 did not enhance NF1-and HNF1␣-mediated activation of the L-PK promoter. 3 The reason for this is unclear, because p300 has been reported to interact with the activation domain of HNF1␣ (39). However, it is possible that other co-activators are involved in cooperative activation of the L-PK gene.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, we consider the interesting possibility that NF1 family members function as coactivators of HNF1␣, although this issue must be further addressed in future studies. There are co-activators with histone acetyltransferase activity that can physically interact with HNF1␣ (38,39). They include p300/cAMP-response element-binding protein, p300/cAMP-response element-binding protein-associated factor, receptor-associated co-activator 3, and steroid receptor co-activator-1.…”
Section: Discussionmentioning
confidence: 99%
“…As p300 has been reported to act as a transcription coactivator for HNF-1α [17], we next studied whether R263L and p300 could cooperatively enhance GLUT2 promoter activity in NIH3T3 cells that has a low p300 expression. Cotransfection of p300 increased GLUT2 promoter activity compared with WT HNF-1α transfection alone.…”
Section: Resultsmentioning
confidence: 99%
“…p300 or CBP also acts as a molecular bridge between transcriptional factors by binding to the activation domain of some transcriptional factors such as CREB as well as multiple components of the basal transcriptional machinery including RNA polymerase II complex [24]. As R263 is not in a region of HNF-1α interacting with p300 that binds to the transactivation domain of HNF-1α [17] and HNF-1α and -1β will interact with each other through their dimerization domains, the R263L mutation should not impair interactions between HNF-1α and p300 or HNF-1β, partly explaining why cotransfection of HNF-1β or p300 increases transcriptional activity of R263L mutant. However, the decreased activity of R263L mutant was not fully rescued by the coexpression with HNF-1β or p300 because R263 in HNF-1α contacts DNA directly regardless of its binding to HNF-1β or p300.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, curcumin decreases diabetes-induced oxidative stress in the kidney through reversion of p300 up-regulation in STZ-treated rats (Chiu et al 2009). Indeed, it has been suggested that abnormal interactions between mutant transcription factors and p300 contribute to the pathogenesis of diabetes (Eeckhoute et al 2001, Fajans et al 2001, Ban et al 2002, Stanojevic et al 2004, Fernandez-Zapico et al 2009). The transcriptional regulation of calt expression in S. aurata does not necessarily apply to human ALT1.…”
Section: Discussionmentioning
confidence: 99%